Comparative in vitro evaluation of N-heterocyclic carbene gold(I) complexes of the benzimidazolylidene type - Rubbiani, Riccardo; Can, Suzan; Kitanovic, Igor; Alborzinia, Hamed; Stefanopoulou, Maria; Kokoschka, Malte; Mönchgesang, Susann; Sheldrick, William S.; Wölfl, Stefan; Ott, Ingo (Journal of medicinal chemistry, 2011)
Gold(I) complexes with a 1,3-diethylbenzimidazol-2-ylidene N-heterocyclic carbene (NHC) ligand of the type NHC-Au-L (L = -Cl, -NHC, or -PPh3) were comparatively evaluated as thioredoxin reductase (TrxR) inhibitors and antimitochondrial anticancer agents. Different effects were noted in various biochemical assays (e.g., inhibition of TrxR, cellular and mitochondrial uptake, or effects on mitochondrial membrane potential), and this was related to properties of the complexes such as bond dissociation energies and overall charge. Remarkable antiproliferative effects, a strong induction of apoptosis, and enhancement of reactive oxygen species (ROS) formation as well as other effects on tumor cell metabolism confirmed the promising potential of the complexes as novel anticancer chemotherapeutics.
Gesehen am 21.09.2022